Development of an achievement test in science I - Palas, Olivia Marasigan (1977)
The study aimed to develop an achievement test that will measure aptitude in Integrated Science I. Item analysis was conducted to determine indices of difficulty and attractiveness of each option. The procedure involved planning the test, constructing and compiling the test items, administering the test, evaluating the test, and preparing the final form of the test. 120 items were prepared for the test which was then administered to 300 sophomore students. Each item was categorized based on the criteria set by Nedelsky, Science Teaching and Testing. The final test was composed of 75 items - 60 good items and 15 fair ones. The index of discrimination ranged from 0.19 to 0.65 while the difficulty index ranged from 0.28 to 0.75. The computed reliability of the test, obtained through the Kuder Richardson Formula 20 is 0.90.